The Role of Forensic Medicine and the Position of Visum et Repertum as Evidence in the Investigation of Persecution: A Case Study of the Kuningan Police Based on Law No. 1 of 2023 - Loevyta Nafishadita; Waluyadi Waluyadi; Gunadi Rasta (Ann Publisher, 2026)
Background. Criminal law enforcement essentially aims to find the material truth through a legitimate evidentiary process. In practice, proof is a very crucial aspect because it determines whether a person can be criminally held accountable or not. In the context of criminal acts of persecution, proof often faces challenges because not all violent incidents can be explained objectively only through witness statements. Purpose. This study aims to analyze the role of Forensic Medicine in the investigation of criminal acts of persecution based on Law Number 1 of 2023 at the Kuningan Police and the position of visum et repertum as evidence in the Examination Report (BAP). Method. This research uses a normative juridical research method with a juridical approach through literature studies, analysis of laws and regulations, legal documents, and a study of Decision Number 33/Pid.B/2026/PN Kng and Examination Minutes (BAP) documents related to persecution cases. Results. The results of the study show that forensic medicine has an important role in supporting the investigation process through the provision of objective scientific evidence regarding the victim's condition. Visum et repertum has a high probative value as evidence of letters as stipulated in Article 235 paragraph (1) of Law Number 20 of 2025. The document plays a role in proving the elements of injury, severity, and causal relationship between the perpetrator's actions and the consequences caused in the criminal act of persecution as stipulated in Article 466 paragraph (1) of Law Number 1 of 2023, as well as strengthening the legal construction of a case. Based on an analysis of laws and regulations, court decisions, and related legal documents, it is known that visum et repertum has a very important position in strengthening criminal evidence, especially in persecution cases. The use of visum et repertum not only helps investigators in compiling the legal construction of the case, but also provides legal certainty in determining the criminal elements that are met. Conclusion. Thus, this study emphasizes that the integration of forensic medicine in the investigation process is an essential need in realizing objective, fair, and science-based law enforcement.